2005
DOI: 10.1158/1541-7786.mcr-05-0221
|View full text |Cite
|
Sign up to set email alerts
|

The Unfolded Protein Response: A Novel Component of the Hypoxic Stress Response in Tumors

Abstract: Hypoxia is a physiologically important endoplasmic reticulum (ER) stress that is present in all solid tumors. Numerous clinical studies have shown that tumor hypoxia predicts for decreased local control, increased distant metastases, and decreased overall survival in a variety of human tumors. Hypoxia selects for tumors with an increased malignant phenotype and increases the metastatic potential of tumor cells. Tumor cells respond to hypoxia and ER stress through the activation of the unfolded protein response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
222
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(233 citation statements)
references
References 101 publications
8
222
0
3
Order By: Relevance
“…We found that phosphorylation of eIF2a also occurs in response to more moderate hypoxia (0.2% and 1% oxygen) but requires significantly longer hypoxic exposures (>8 hours). Several additional reports have confirmed the increase in eIF2a phosphorylation during both severe and moderate hypoxic exposures (27)(28)(29).…”
Section: Perk-eukaryotic Initiation Factor 2a Control Of Translation mentioning
confidence: 79%
“…We found that phosphorylation of eIF2a also occurs in response to more moderate hypoxia (0.2% and 1% oxygen) but requires significantly longer hypoxic exposures (>8 hours). Several additional reports have confirmed the increase in eIF2a phosphorylation during both severe and moderate hypoxic exposures (27)(28)(29).…”
Section: Perk-eukaryotic Initiation Factor 2a Control Of Translation mentioning
confidence: 79%
“…The accumulation of misfolded proteins disturbs cellular redox regulation and stimulates the production of endogenous ROS [27], leading to the activation of ER stress signals and ER dysfunction. In response to increased ROS levels, the ER elicits a series of effector signals known as the UPR to adapt to the changing environment and restore ER function and homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…It activates a subsequent mechanism to promote cellular proliferation and blocks programmed cell death. 29,30 Malignant cells are permanently exposed to stress, mainly induced by hypoxic conditions and glucose deprivation caused by poor vascularization in their metabolic microenvironment, 35,36 and to immunological attacks. 37,38 For their survival, they have to adapt their cellular turnover to a higher need of nutrition and energy.…”
Section: Discussionmentioning
confidence: 99%